Food insecurity among postsecondary international students: a scoping review protocol. Issue 10 (13th October 2022) - Amoyaw, Jonathan; Pandey, Mamata; Maina, Geoffrey; Li, Yiyan; Nkrumah, Daniel Owusu
Abstract : Introduction: International students make significant contributions to their host institutions and countries. Yet research shows that not all international students have the financial means to fend for themselves and meet their financial obligations for the entire study programme. Such students are at significant risk of food insecurity. The objective of this scoping review is to synthesise available information on the factors related to food insecurity among international students studying at postsecondary educational institutions and identify the types of food insecurity interventions that have been implemented to address this issue. Methods and analysis: The Joanna Briggs Institute scoping review methodology will be used to guide this scoping review, and we will search the following databases: MEDLINE (through Ovid), CINAHL (EBSCO), PubMed, ERIC (via Ovid), PROSPERO and ProQuest. The titles, abstracts, and subsequently full texts of the selected papers will then be screened against the inclusion criteria. Data from articles included in the review will be extracted using a data charting form and will be summarised in a tabular form. Thematic analysis will be used to identify common themes that thread through the selected studies and will be guided by the steps developed by Terry et al . Ethics and dissemination: Since this project entails a review of available literature, ethical approval is not required. The findings will be presented at academic conferences and published in a peer-reviewed journal. To make the findings more accessible, they will also be distributed via digital communication platforms.